Biología reproductiva de Eschweilera bogotensis (Lecythidaceae), en la Cordillera Occidental de Colombia - Gamboa Gaitán Miguel Ángel (Caldasia)
The reproductiva biology of Eschweilera bogotensis (Lecythidaceae) was studied in a premontane forest at Los Farallones de Cali National Park (1650 m) from november 1993 to march 1994. A great number of insects visit the flowers of this tree. Curculionidae and Nitidulidae (Coleoptera) larvae, as well as Cecidomyidae (Diptera) larvae feed on immature flowers, while Pyralidae and Blastobasidae (Lepidoptera) larvae eat ripening fruits. Adult individual s of Staphylinidae (Coleoptera) and Phlaethripidae (Thysanoptera) were observed feeding on pollen. Loss of floral buds due to larval parasitism was as high as 70%. Three species of Hymenoptera were identified as visitors: Trigona amalthea, Eulaema meriana (Apidae), and Epicharis rustica (Anthophoridae). The latter was identifiedas the main pollinator. Fruit set per inflorescence is quite low (three max.), and over 50% of inflorescences get lost. Seed release is carried out by transversal dehiscence of the fruit, releasing 4-7 seeds. Seed dispersal by animals, which eat part of the peel and seeds, is significant. Bites on the fruits observed in the field suggest that the disperser is a rodent, probably a squirrel, common at the study site. Germination of bitten seeds was observed. Se estudió la biología reproductiva de Eschweilere bogotensis (Lecyhidaceae), en un bosque muy húmedo premontano del Parque Nacional Los Farallones de Cali (1650 m), entre noviembre de 1993 y marzo de 1994. Numerosos insectos visitan las inflorescencias de este árbol. Las larvas de Curculionidae, Nitidulidae (Coleoptera) y Cecidomyidae (Diptera) depredan flores inmaduras, mientras que las de Pyralidae y Blastobasidae (Lepidoptera) depredan frutos maduros. También se observaron adultos de Staphylinidae (Coleoptera), los cuales se alimentan de polen al igual que los Phlaethripidae (Thysanoptera). Las pérdidas de botones florales por parasitismo alcanzaron el 70%. Se identificaron tres especies de himenópteros como visitantes regulares: Trigona amalthea, Eulaema meriana (Apidae) y Epicharis rustica (Anthophoridae). Este último es el principal agente polinizador. La fructificación por inflorescencia es muy baja (tres máximo), y más del 50% de las inflorescencias se pierden en su totalidad. La liberación de las semillas se hace mediante dehiscencia transversal del fruto, liberándose de 4 a 7 semillas. La dispersión por animales, los cuales consumen parte de la cáscara y semillas, es significativo. Por las huellas de mordeduras observadas en el campo, se asume que el agente dispersor es un roedor, muy probablemente una ardilla, animal común en la zona. Se ha comprobado la germinación de semillas mordidas.